The Connotative Use of Kinship Terms for Non-Kins as Social Honorifics in Contemporary Algerian Dialect - Merzouk, Rekia (My University, 2017)
Within the domain of socio-pragmatic studies of language also within the theories of communication, social honorifics are viewed as the encoding of social information in human interactions including pronouns and titles of address. The present paper is concerned mainly with studying kinship terms as social honorifics. Furthermore, they are denotationally terms used to address relatives (referring to ties based on blood and marriage). However, we are interested in the connotative use of kinship terms to address strangers in non-kin interactions within the Algerian society. Our aim through conducting this study is to focus more on the connotative use of kinship terms in contemporary Algerian dialect shedding light on which terms are used among Algerians more to address non-relatives, to whom they address and for which reasons. This paper explores the main forms and categories of social honorifics in general and more specifically kinship terms as honorific terms. Moreover, we are investigating through this study the denotative meaning of kinship terms but focusing more on the connotative one as the main interest.
Keywords: Social honorifics; Kinship terms; Connotative; Non-kins; Strangers; Politeness; Solidarity; Contemporary Algerian dialect